2001
DOI: 10.1034/j.1600-0773.2001.d01-93.x
|View full text |Cite
|
Sign up to set email alerts
|

The Ototoxic Effects Induced in Rats by Treatment for 12 Weeks with 2‐Butenenitrile, 3‐Butenenitrile and cis‐2‐Pentenenitrile

Abstract: Brainstem auditory and visual evoked-potentials were studied in male Sprague-Dawley rats during subchronic oral treatment with three unsaturated aliphatic nitriles. The rats were given, by gastric intubation, doses of 10, 20 and 40 mg ¡ kg ª1 3-butenenitrile (allyl cyanide) and 25, 50 and 100 mg ¡ kg ª1 of either cis/trans-2-butenenitrile (crotononitrile) or cis-2-pentenenitrile once a day, 5 days per week for 12 weeks. Oral administration of the three unsaturated nitriles produced deafness and absence of reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
(29 reference statements)
2
14
0
Order By: Relevance
“…In the present study, we did not assess the effect of cis-crotononitrile and allylnitrile on the auditory system. However, in the rat, both nitriles have been demonstrated to cause hearing loss and cochlear hair cell degeneration (Gagnaire et al 2001;Balbuena andLlorens 2001, 2003), with similar dose-response relationships between cochlear and vestibular damage. Further studies are required to assess whether the present exposure models result in useful cochlear damage in addition to the assessed vestibular damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we did not assess the effect of cis-crotononitrile and allylnitrile on the auditory system. However, in the rat, both nitriles have been demonstrated to cause hearing loss and cochlear hair cell degeneration (Gagnaire et al 2001;Balbuena andLlorens 2001, 2003), with similar dose-response relationships between cochlear and vestibular damage. Further studies are required to assess whether the present exposure models result in useful cochlear damage in addition to the assessed vestibular damage.…”
Section: Discussionmentioning
confidence: 99%
“…standing need in inner ear research, for example, in studies to develop strategies for alleviating human labyrinth damage by hair cell protection, regeneration, or replacement. One possible model is exposure to the nitriles allylnitrile and cis-crotononitrile, with a known ototoxic potential (Balbuena andLlorens 2001, 2003;Gagnaire et al 2001;Soler-Martín et al 2007;Boadas-Vaello et al 2007Saldaña-Ruíz et al 2012a). In this study, we have evaluated refining these models through the use of pharmacological agents that inhibit the CYP2E1 enzyme to reduce the acute systemic toxicity of the nitriles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many nitriles are known to cause acute toxicity through cyanide release by xenobiotic metabolism enzymes, a toxic endpoint already addressed by some modeling studies (Grogan et al, 1992). The work by several groups, including ours, has demonstrated that several nitriles cause a variety of neurotoxic effects, such as degeneration of specific populations of neurons in the central nervous system (Boadas-Vaello et al, 2005;Seoane et al, 2005) and degeneration of sensory systems including the olfactory (Genter et al, 1992), auditory (Gagnaire et al, 2001) and vestibular systems (Llorens et al, 1993;Llorens, 2001, 2003). We have observed that vestibular toxicity is not related to cyanide release (Boadas-Vaello et al, 2007) and is associated with strict structural requirements (Balbuena and Llorens, 2003) that may depend on the animal species, as the case of trans-crotononitrile, which causes neuronal degeneration in the rat (Boadas-Vaello et al, 2005;Seoane et al, 2005) and vestibular toxicity in the mouse (Saldaña-Ruíz et al, 2012).…”
Section: Regulatory Neurotoxicity Testing For Risk Assessment Purposementioning
confidence: 99%
“…Among sensory systems, the inner ear is a major target for several nitriles: degeneration of the vestibular and/or auditory sensory hair cells has been reported in rodents exposed to 3,3'-iminodipropionitrile (IDPN) (Llorens et al, 1993;Llorens and Demêmes, 1994;Crofton et al, 1994;Soler-Martín et al, 2007), allylnitrile (Balbuena and Llorens, 2001;Gagnaire et al, 2001), racemic crotononitrile (Llorens et al, 1998;Gagnaire et al, 2001), and cis-crotononitrile (Balbuena and Llorens, 2003). IDPN has also been shown to cause vestibular toxicity in frogs (Soler-Martin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%